Adult-Onset Neuronal Ceroid Lipofuscinosis With a Novel DNAJC5 Mutation Exhibits Aberrant Protein Palmitoylation - Huang, Qiang; Zhang, Yong-Fang; Li, Lin-Jie; Dammer, Eric B.; Hu, Yong-Bo; Xie, Xin-Yi; Tang, Ran; Li, Jian-Ping; Wang, Jin-Tao; Che, Xiang-Qian; Wang, Gang; Ren, Ru-Jing (Frontiers in Aging Neuroscience, 2022)
Neuronal ceroid lipofuscinosis (NCL) is a group of inherited neurodegenerative diseases, with the hallmark of accumulation of lipofuscin (a mixture of lipids and proteins together with mental) inside lysosomal lumen which typically emits auto-fluorescence. There has been reports about L115R and L116Δ mutation in the DNAJC5 gene for patients with NCL. In this study, we reported a novel C128Y mutation in a young Chinese female, and this novel mutation caused abnormal palmitoylation and triggered lipofuscin deposit in vitro and in vivo.